Does Environmental Degradation-Led Remittances Flow? Nexus between Environmental Degradation, Uncertainty, Financial Inclusion and Remittances Inflows in India and China - Qamruzzaman, Md. (International Journal of Energy Economics and Policy, 2023)
The motivation of the study is to gauge the role of economic policy uncertainty (EPU), environmental degradation (ED), and financial inclusion (FI) on remittances in India and China for the period 2003Q1-2022Q1. The study performed several econometrical tools such as both conventional and structural break unit root tests, long-run cointegration between variables investigative by performing the novel combined cointegration test, augmented autoregressive distributed lagged (AARDL) implemented for exploring long-run cointegration and explanatory variables magnfititutes on remittances both in the long-run and short-run and directional causality performed with Fourier TY causality test. Combined cointegration and the AARDL test ascertained the long-run association in the empirical equation. Refers to long-run coefficients of EPU, ED, and FI, it revealed a positive and statistically significant linkage with remittance inflows in the economy. In addition, the causality test reveals directional effects available between FDI, GLO, and remittances, but the direction differs from among economics. Furthermore, the study performed a robustness test by implementing dynamic OLS, fully modified OLS and CC regression and supported the earlier model established relationship, especially in the long-run the coefficients of EPU, ED, and FI.